Impact of corporate social responsibility on customer loyalty behaviors: evidence from Vietnam - Ngo, Thanh Thanh Huyen (2020)
The study investigated how corporate social responsibility (CSR) performance including towards society, environment and stakeholders affect brand likeability and relational switching cost. Concurrently, the relationship between brand likeability and relational switching cost and customer loyalty behaviors including word-of-mouth and repurchase intention. The study’s sample size is 212 responses from Vietnamese respondents. The hypotheses are tested by regression analysis through SPSS software. The findings show CSR practice affects brand likeability and relational switching cost. However, the effect is different in term of degree. When looking into the relationship between CSR dimensions and brand likeability, CSR towards stakeholders is a more significant predictor than others while CSR towards environment and society are supposed to have more remarkable impact on relational switching cost. Additionally, brand likeability and relational switching cost positively affect word of mouth and repurchase intention. Brand likeability has more significant influence on word of mouth while both brand likeability and relational switching cost affect nearly equally repurchase intention.